2023
DOI: 10.3390/biology12040571
|View full text |Cite
|
Sign up to set email alerts
|

Boundaries Are Blurred: Wild Food Plant Knowledge Circulation across the Polish-Lithuanian-Belarusian Borderland

Abstract: The circulation of local ecological knowledge (LEK) is a promising avenue of research for wild plant studies. To encourage the acceptance, celebration, and appreciation of biocultural diversity, which is rapidly disappearing nowadays, we need to estimate and assess multifaceted local ecological knowledge. It has direct application for local communities in informing effective policies for improving food security and building community-specific responses to environmental and social transitions. The present study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…The cross-border JIs in DiGe studies [10] varied from 65 among Setos in Estonia and Russia, where the border was merely administrative until 30 years ago [35], to 55 among Hutsulsin Romania and Ukraine, where the solid border was established over 75 years before the study [8]. At the same time, the Polish-Belarus-Lithuanian borderlands ranged from 48 to 62, as in that once homogenous region, the borders shifted several times in the last 75 years [20]. Therefore, the cross-border JI between Hawraman Iran and Iraq stays within the results obtained in DiGe studies [10].…”
Section: Transitional Knowledge Over State Borders: Differences and S...mentioning
confidence: 99%
See 1 more Smart Citation
“…The cross-border JIs in DiGe studies [10] varied from 65 among Setos in Estonia and Russia, where the border was merely administrative until 30 years ago [35], to 55 among Hutsulsin Romania and Ukraine, where the solid border was established over 75 years before the study [8]. At the same time, the Polish-Belarus-Lithuanian borderlands ranged from 48 to 62, as in that once homogenous region, the borders shifted several times in the last 75 years [20]. Therefore, the cross-border JI between Hawraman Iran and Iraq stays within the results obtained in DiGe studies [10].…”
Section: Transitional Knowledge Over State Borders: Differences and S...mentioning
confidence: 99%
“…Different cultures often develop specific recipes using distinct ingredients [18]. The underlying ecological knowledge is shaped by many factors, including sociocultural aspects such as religion, language, politics, governmental systems, and economic features [15,19,20]. In the comparisons conducted by the DiGe project [10], the cross-border differences in the wild food plant uses are often more pronounced than in the comparison between the cultural groups, differing in several aspects (ethnic, linguistic, and religious) but residing in the same country [12,18].…”
Section: Introductionmentioning
confidence: 99%
“…The main environmental reason behind the abandonment of foraging is plant availability. A decreased abundance of wild plants was observed by several authors [69,102,110,111], frequently attributed to changing climate [79,88,90] or the disappearance of the place of growth following ecosystem changes [56,93,96,112,113]. Some elderly informants reported that landscape changes such as forest expansion and decreased coppices or agricultural intensification are among the anthropogenic land-use changes responsible for this reduction [58,107,109,114], and others blame the practice of intensive mowing [90,113] as well as the increased use of chemical products as responsible [57,83].…”
Section: Environmental Reasonsmentioning
confidence: 99%
“…People still consume plants because of their past role in the community and because they are linked to their ethnic identity [55,61,101]. Even when traditional plants do not grow anymore in the wild, people have started to buy them [111], thus showing their cultural importance. The persistence of these practices binds the present society with the positive aspects of their origin [107].…”
Section: Cultural Motivationsmentioning
confidence: 99%
See 1 more Smart Citation